Organ-specific accumulation of cadmium and zinc in Gammarus fossarum exposed to environmentally relevant metal concentrations. (1st September 2022) - Gestin, Ophélia; Lopes, Christelle; Delorme, Nicolas; Garnero, Laura; Geffard, Olivier; Lacoue-Labarthe, Thomas
Abstract: One of the best approaches for improving the assessment of metal toxicity in aquatic organisms is to study their organotropism (i.e., the distribution of metals among organs) through a dynamical approach (i.e., via kinetic experiments of metal bioaccumulation), to identify the tissues/organs that play a key role in metal regulation (e.g., storage or excretion). This study aims at comparing the organ-specific metal accumulation of a non-essential (Cd) and an essential metal (Zn), at their environmentally relevant exposure concentrations, in the gammarid Gammarus fossarum . Gammarids were exposed for 7 days to 109 Cd- or 65 Zn-radiolabeled water at a concentration of 52.1 and 416 ng.L −1 (stable equivalent), respectively, and then placed in clean water for 21 days. At different time intervals, the target organs (i.e., caeca, cephalons, intestines, gills, and remaining tissues) were collected and 109 Cd or 65 Zn contents were quantified by gamma-spectrometry. A one-compartment toxicokinetic (TK) model was fitted by Bayesian inference to each organ/metal dataset in order to establish TK parameters. Our results indicate: i) a contrasting distribution pattern of concentrations at the end of the accumulation phase (7 th day): gills > caeca ≈ intestines > cephalons > remaining tissues for Cd and intestines > caeca > gills > cephalons > remaining tissues for Zn; ii) a slower elimination of Cd than of Zn by all organs, especially in the gills in which the Cd concentration remained constant during the 21-day depuration phase, whereas Zn concentrations decreased sharply in all organs after 24 h in the depuration phase; iii) a major role of intestines in the uptake of waterborne Cd and Zn at environmentally relevant concentrations. Graphical abstract: Image 1 Highlights: Uptake and depuration kinetics parameters were assessed by one-compartment TK modelling. The ku and ke were significantly lower for Cd than for Zn, except for ku of gills. In depuration, Cd is slowly eliminated by organs and Zn decreases sharply in 24 h. No elimination of Cd was measured in gills after a 21-day depuration phase. Intestine is dominant uptake and depuration path for Cd and Zn in dissolved exposure.